Expected time to rendezvous in multi-hop cognitive radio networks - Ortiz Guerra, Erik; Suarez Mora, David; Lopez, Edgar Alexander; Alfonso Reguera, Vitalio; Blanco Garrido, Fabian; Cruz Flores, Liliana (My University, 2017)
The design of blind rendezvous strategies for dy- namic spectrum access in multi-users, multi-hop networks is a challenging task. In this paper, a two radios synchronization strategy that minimizes the time to rendezvous in multi-users networks is analyze. In fact, it has been recently demonstrated that this synchronization strategy provides optimum results in terms of maximum time to rendezvous (MTTR). In this paper, the analysis to the expected time to rendezvous (ETTR) and derive analytical expressions for its numerical computation is extended. The estimated ETTR is compared with those obtained by simulation, using a representative blind rendezvous channel hopping sequence. The results indicate that the numerical ex- pressions provide good estimates of the actual ETTR. Moreover, the ETTR achieved by the proposed synchronization strategy has proven to be bounded by the MTTR of a pair-wise rendezvous process irrespective of the number of users and the network topology. This property makes the analyzed rendezvous mecha- nism, and particularly the synchronization strategy, suitable for the deployment of large and dense networks.
Keywords: Blind Rendezvous; Channel Hopping Sequences; Cognitive Radio Networks; Multi-Hop Networks